FROM “CHOLO SOTIL” TO “CHOLA CHABUCA” Seen from schools in popular sectors of Lima - Jacinto Pazos, Pedro (2020)
A concept that grabs violence, conflict and racial discrimination is the idea of ​​“cholo o chola” (people with indigenous ancestry). A group of people who had a direct participation in society were chosen, such as a group of secondary school students. Due to their long process of continuous interrelation and permanent socialization in the classroom, it is possible to analyse and explain how these students observe in school the so-called ​​“cholo o chola” from the main personalities in the world of football, music, as well as in the Peruvian television comic programs. In fact, the reason was to relate social spaces that involve all media, where social actors are graphed in intercultural contexts, which at the same time, are characteristic of our ethnic-cultural diversity, but where also, racial discrimination and socio-cultural exclusion are still present. Fifth year high school students from two schools in Lima were interviewed. The first one in San Juan de Lurigancho and the other, in Villa María del Triunfo.